Quantitative measurement of JWH-018 and JWH-073 metabolites excreted in human urine - Moran, Cindy L; Le, Vi-Huyen; Chimalakonda, Krishna C; Smedley, Amy L; Lackey, Felisia D; Owen, Suzanne N; Kennedy, Paul D; Endres, Gregory W; Ciske, Fred L; Kramer, James B; Kornilov, Andrei M; Bratton, L D; et al. (Analytical chemistry (Washington), 2011)
"K2/SPICE" products are commonly laced with aminoalkylindole synthetic cannabinoids (i.e., JWH-018 and JWH-073) and are touted as "legal" marijuana substitutes. Here we validate a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for measuring urinary concentrations of JWH-018, JWH-073, and several potential metabolites of each. The analytical procedure has high capacity for sample throughput and does not require solid phase or liquid extraction. Evaluation of human urine specimens collected after the subjects reportedly administered JWH-018 or a mixture of JWH-018 and JWH-073 provides preliminary evidence of clinical utility. Two subjects that consumed JWH-018 primarily excreted glucuronidated conjugates of 5-(3-(1-naphthoyl)-1H-indol-1-yl)-pentanoic acid (>30 ng/mL) and (1-(5-hydroxypentyl)-1H-indol-3-yl)(naphthalene-1-yl)-methanone (>50 ng/mL). Interestingly, oxidized metabolites of both JWH-018 and JWH-073 were detected in these specimens, suggesting either metabolic demethylation of JWH-018 to JWH-073 or a nonreported, previous JWH-073 exposure. Metabolic profiles generated from a subject who consumed a mixture of JWH-018 and JWH-073 were similar to profiles generated from subjects who presumably consumed JWH-018 exclusively. Oxidized metabolites of JWH-018 and JWH-073 were of the same pattern, but JWH-018 metabolites were excreted at lower concentrations. These results begin clinically validating the LC-MS/MS assay for detecting and quantifying aminoalkylindole metabolites. Full validation awaits further testing.